Evaluation of travel time and speed on mid-block urban street using computer simulation models / Ahmad Fairuz Othman - Othman, Ahmad Fairuz (2010)
With the ever increasing technological improvement to personnel computers, traffic simulation approach has been gaining popularity in applications of traffic operation analyses. Simulation is easily executed on the personal computer and is gaining favour with practitioners. Therefore by developing and tailored made one’s own software through effort and initiative, one will be able to develop an understanding of how simulation software work and as a tool that can help to overcome local traffic issues. The primary aims of this study are to evaluate the microscopic traffic operation model such as travel time and average spot speed based on computer simulation. Computer simulation based on car following theory was developed based on empirical traffic data and then incorporated into computer modeling. In the simulation development process, validation with site empirical data was compared with simulation output using paired T-test and discrepancy measure such as MSE, MAE, and MAPE. In the next stage the simulation output was then checked and validated with established model from Transportation of Research Board, 2000.